The band structures of three-dimensional nonlinear plasma photonic crystals - Hai-Feng Zhang (AIP Advances, 2018)
In this paper, the properties of the photonic band gaps (PBGs) for three-dimensional (3D) nonlinear plasma photonic crystals (PPCs) are theoretically investigated by the plane wave expansion method, whose equations for calculations also are deduced. The configuration of 3D nonlinear PPCs is the Kerr nonlinear dielectric spheres (Kerr effect is considered) inserted in the plasma background with simple-cubic lattices. The inserted dielectric spheres are Kerr nonlinear dielectrics whose relative permittivities are the functions of the external light intensity. Three different Kerr nonlinear dielectrics are considered, which can be expressed as the functions of space coordinates. The influences of the parameters for the Kerr nonlinear dielectrics on the PBGs also are discussed. The calculated results demonstrate that the locations, bandwidths and number of PBGs can be manipulated with the different Kerr nonlinear dielectrics. Compared with the conventional 3D dielectric PCs and PPCs with simple-cubic lattices, the more PBGs or larger PBG can be achieved in the 3D nonlinear PPCs. Those results provide a new way to design the novel devices based on the PPCs.